Aboriginal Gambling and Problem Gambling: A Review - Breen, Helen (Springer-Verlag, 2012)
The prevention of gambling-related problems amongst Aboriginal communities has been neglected by most public health strategies which concentrate on mainstream populations. Research indicates that rates of problem gambling are higher for Aboriginal groups than the general population. Specific cultural, familial, and social patterns influence gambling by Aboriginal groups, which are individually different, making it difficult to implement a cohesive strategy to address gambling-related harms. Because of this complexity, a thorough literature review is necessary to identify gaps in policy and research. This paper uses a public health framework to consider multi-dimensional influences (personal, environmental, economic, cultural and social) that affect gambling uptake. Such analysis is also important for identifying risk factors which facilitate the development and maintenance of problem gambling and potentially for underpinning protection, prevention and treatment programs. It is advised that strategies be developed in consultation with Aboriginal peoples to guide public health policy and research to minimise any gambling-related harms.